2012
DOI: 10.1002/ardp.201200125
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Benzophenone O‐Glycosides as α‐Glucosidase Inhibitors

Abstract: The first total synthesis of benzophenone O-glycosides (iriflophenone 2-O-α-L-rhamnopyranoside: 1 and aquilarisinin: 2) isolated from the leaves of Aquilaria sinensis and related new derivatives (3-12) was accomplished through suitable protecting group manipulations and glycosylation starting from commercially available L-rhamnose, D-glucose, D-galactose, D-mannose, D-xylose, and 1,3,5-trihydroxybenzene. All synthesized benzophenone O-glycosides were evaluated for their inhibitory activities against α-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In a series of our studies on in vitro PTP1B and a-glucosidase-inhibiting principles from synthetic natural products and derivatives, we previously reported the efficient artificial synthesis of sugarsubstituted oleanolic acid derivatives, hederagenin glycosides, natural benzophenone O-glycosides, and their derivatives. The structure-activity relationships (SARs) of these saponins showed that the sugar moiety strongly influenced PTP1B and a-glucosidase inhibitory activities, and also improved their inhibition against murine in vivo glucose absorption [34][35][36][37]. As part of an ongoing investigation, here we report the synthesis, a-glucosidase and a-amylase inhibitory activities, and SARs of naturally occurring oleanane-type triterpenoid saponins (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)15, and 16) [38][39][40][41][42][43] and non-natural oleanolic acid saponins (2-4 and 14) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of our studies on in vitro PTP1B and a-glucosidase-inhibiting principles from synthetic natural products and derivatives, we previously reported the efficient artificial synthesis of sugarsubstituted oleanolic acid derivatives, hederagenin glycosides, natural benzophenone O-glycosides, and their derivatives. The structure-activity relationships (SARs) of these saponins showed that the sugar moiety strongly influenced PTP1B and a-glucosidase inhibitory activities, and also improved their inhibition against murine in vivo glucose absorption [34][35][36][37]. As part of an ongoing investigation, here we report the synthesis, a-glucosidase and a-amylase inhibitory activities, and SARs of naturally occurring oleanane-type triterpenoid saponins (1,(5)(6)(7)(8)(9)(10)(11)(12)(13)15, and 16) [38][39][40][41][42][43] and non-natural oleanolic acid saponins (2-4 and 14) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes was induced in rats by a single intraperitoneal injection of freshly prepared alloxan solution in normal saline at a dose of 150 mg/kg body weight 6. After 2 weeks, the rats whose blood glucose was higher than 2 g/L were chosen for the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…It is generally recognized that patients with diabetes are at risk for numerous severe complications, including diabetic hyperlipidemia, liver–kidney complications, and hypertension 2–4. One of the therapeutic approaches for decreasing hyperglycemia and obesity is to retard absorption of glucose by the inhibition of carbohydrate‐hydrolyzing enzymes such as α‐amylase and α‐glucosidase, in the digestive organs 5, 6. Screening of α‐glycosidase inhibitors is becoming increasingly attractive because α‐glycosidases are responsible for the processing and hydrolysis of complex carbohydrates into absorbable simple sugar in the small intestine 2–5.…”
Section: Introductionmentioning
confidence: 99%
“…Iriflophenone 2-O-α-L-rhamnopyranoside (1) was obtained as a yellowish amorphous powder. The 1 H and 13 C NMR spectra of 1 showed features of a benzophenone glycoside [8,9]. In detail, the 1 H NMR spectrum showed six aromatic protons [δ 7.59 (2H, d, J = 8.4 Hz, H-2՛,6՛), 6.81 (2H, d, J = 8.4 Hz, H-3՛,5՛), 6.30 (1H, br s, H-3), 6.08 (1H, br s, H-5)] accounting for a p-disubstituted benzene ring and a tetrasubstituted benzene ring.…”
mentioning
confidence: 99%